2019
DOI: 10.1016/j.cub.2019.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Striga asiatica Provides Insight into the Evolution of Plant Parasitism

Abstract: Highlights d The Striga genome reflects a three-phase model of parasitic plant genome evolution d A family of strigolactone receptors has undergone a striking expansion in Striga d Genes in lateral root development are coordinately induced in a parasitic organ d Host genes and retrotransposons are horizontally transferred into Striga

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
187
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(195 citation statements)
references
References 68 publications
8
187
0
Order By: Relevance
“…We found that several GO terms, such as “lipid metabolic process” and “carbohydrate metabolic process”, are strongly enriched in the rest of the haustorium but not in the intrusive cells (Supplemental Tables S1 and S2). Yoshida et al . (2019) showed that genes categorized under the GO terms “protein metabolic process”, “carbohydrate metabolic process”, and “catabolic process” are upregulated in rice-infecting Striga hermonthica at 7 dpi, when the host-parasite connection in the haustorium is established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that several GO terms, such as “lipid metabolic process” and “carbohydrate metabolic process”, are strongly enriched in the rest of the haustorium but not in the intrusive cells (Supplemental Tables S1 and S2). Yoshida et al . (2019) showed that genes categorized under the GO terms “protein metabolic process”, “carbohydrate metabolic process”, and “catabolic process” are upregulated in rice-infecting Striga hermonthica at 7 dpi, when the host-parasite connection in the haustorium is established.…”
Section: Discussionmentioning
confidence: 99%
“…S6). Interestingly, the only other gene with experimentally confirmed expression in intrusive cells encodes a peroxidase in S. hermonthica (Yoshida et al ., 2019). Also, chemically inhibiting peroxidase activity, and thus altering the redox homeostasis, reduces haustorium formation in Striga spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, no other parasitic effectors have been clearly characterized. The genome sequences of Striga asiatica (Yoshida et al , 2019), Orobanche cumana (S. Munos & P. Delavault, unpublished), and P. ramosa (S. Wicke, unpublished) should provide valuable data to seek such potential effector proteins and some studies seem to support their existence. Hegenauer et al .…”
mentioning
confidence: 99%